Dampak Dampak Pencemaran Pantai Tapak Paderi Kota Bengkulu Akibat Sampah Terhadap Kelestarian Laut di Indonesia - Sari, Resi Purnama; Sunarti, Nefi Ratna; Walid, Ahmad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Bengkulu Province is one of 34 provinces in Indonesia which has a coastline of 7 KM. Along the 7 KM beach has a range of different names, ranging from the long beach, beach file beach, tofu beach, paderi beach, and the beach of kualo. Not only that, there are still many beaches in Bengkulu because Bengkulu province is surrounded by a vast ocean. This is what attracts tourists both local and foreign. But what would be if there was one of the beaches there was a vast stretch of community trash? Will there still be many visitors who come? The large amount of rubbish that is disposed of carelessly is on the beach of the paderi tread. Various types of rubbish are found along the coast of the paderi tread. This can make visitors less interested due to too much garbage, not only that beach water can be polluted due to garbage that contains a lot of chemicals. If not handled early, the existing marine biota could die due to polluted coastal water. It is necessary to intervene from the environmental service to be able to cope with the rubbish on the beach. In order to return the preservation of the beach tapak paderi.